INFLUÊNCIA DO CONTROLE QUÍMICO DAS DOENÇAS FOLIARES E A INCIDÊNCIA DE MICRORGANISMOS EM BULBOS DE CEBOLA ARMAZENADOS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2009)
This work presents the results of two experiments that were carried out with the objective of evaluating the of fungicides in the control of foliar diseases on onion crops. Also, it was verified the influence of hose fungicides sprayed over the leaves at the post-planting up to the pre-harvest phase in the reduction of the post-harvest diseases. In the bulb production trial the cultivars Vitória, Bola Precoce and Montana were avaluated. The experiment was designed with10tratments such as: Control (no spray); 0,5 L/ha of Difenoconazol; 1,0 L/ha of Tebuconazol; 0,75 L/ha of Tebuconazol + Trifloxistrobina; 0,4 L/ha of Difenoconazol + Azoxistrobina; 0,12 kg/ha of Azoxistrobina ; 0,16 kg/ha of Azoxistrobina; 2,0 kg/ha of Pyraclostrobina + Metirana;0,4 L/ha of Cyprodinil; and 2,0 kg/ha of Cyprodinil + Fludioxonil with four replications. For each replication, 10 plants were randomized selected and weekly analized in order to check the total number of leaves, number of leaves with pathogens lesion and severity levels of the pathogens on the onions`s leaves . To the yield evaluation, an area of 7,8 m² for each replication was harvested, weighted and the data transformed to kg/ha. On the post-harvest experiment, 100 bulbs per treatment were ramdomnly selected, being 25 bulbs per replication, and then stored in a packing house under local environmental conditions. The bulbs were evaluated each 30days, by measuring their weight, number of bulbs with pathogens and the eliminate bulbs, respectively. All treatments with fungicides were capable to reduce the incidence of Alternaria porri on the onion leaves and produced a lower number of leaves with A. porri symptoms. Generally speaking, all fungicides treatments were able to increase productivity, with exception to the Montana cultivar. The fungicides sprayed for controlling the onion`s leaves against pathogens attacks had also a positive effect on the incidence of the post-harvest pathogens during of onion bulbs. The Bola Precoce cultivar presented the lowest pathogen incidence as well as percentage of eliminated bulbs. The treatments of fungicides sprayed over the onion`s leaves at field condition when tested for postharvest bulbs conservation, were less effective for the Bola Precoce cultivar when compared to Montana and Vitória ones.
Keywords: Allium cepa; Alternaria porri; Botritis spp, pós-colheita; fungicidas; Allium cepa; Alternaria porri; Botritis spp, post-harvest; fungicides; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA